If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -6 + y + 24 = 8y + 20 + -6y Reorder the terms: -6 + 24 + 3y + y = 8y + 20 + -6y Combine like terms: -6 + 24 = 18 18 + 3y + y = 8y + 20 + -6y Combine like terms: 3y + y = 4y 18 + 4y = 8y + 20 + -6y Reorder the terms: 18 + 4y = 20 + 8y + -6y Combine like terms: 8y + -6y = 2y 18 + 4y = 20 + 2y Solving 18 + 4y = 20 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 18 + 4y + -2y = 20 + 2y + -2y Combine like terms: 4y + -2y = 2y 18 + 2y = 20 + 2y + -2y Combine like terms: 2y + -2y = 0 18 + 2y = 20 + 0 18 + 2y = 20 Add '-18' to each side of the equation. 18 + -18 + 2y = 20 + -18 Combine like terms: 18 + -18 = 0 0 + 2y = 20 + -18 2y = 20 + -18 Combine like terms: 20 + -18 = 2 2y = 2 Divide each side by '2'. y = 1 Simplifying y = 1
| 38=6x-16 | | 12X+X-5X-2=0 | | m-61=39 | | 6-2x=5x-9+12 | | m/15=1/3 | | -16+49x^2=0 | | 5m-6=35 | | 4=k-6 | | 2+x=9 | | x^2+13xy+36y=0 | | 4(4x+1)-8(x-2)=3(2x+5)-2 | | 4x^2-2x-9=0 | | 10m-6=20 | | -17+x-14= | | 11x^2+3x+2=0 | | -10+3x=-19 | | -17=z-21 | | x*x+x-4=0 | | xx+x-4=0 | | 169-4x=41x+19 | | 6x+1=-65 | | 8x+20=6x+13 | | (4x^3+6x-6)+(9x^2-7x+4)= | | x=36/3 | | 8k+20=6k | | 6x^2+10x=-21x-35 | | 14-9x=86-23x | | -2+7x=40 | | x^2-50=-23x | | 4.5+x-4= | | x=9*9 | | x=6*6*6 |